Pengaruh Skeptisisme Audit, Kompetensi Auditor Dan Tekanan Anggaran Waktu Terhadap Kualitas Audit: (Studi Empiris pada Kantor Akuntan Publik di Wilayah Jakarta Selatan dan Jakarta Timur) - Cut Zia Auralia; Amor Marundha; Maidani Maidani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to measure the influence of Audit Skepticism, Auditor Competence and Time Budget Pressure on Audit Quality at Public Accounting Firms (KAP) in the South Jakarta and East Jakarta Regions. This research was conducted using a non-probability sampling approach with a purposive sampling method. The number of samples used in this research was 77 respondents. The design used in this research is hypothesis testing using the Structural Equitation Model (SEM) - SmartPLS v. 3.2.9. The results of this research indicate that (1) Audit Skepticism has a positive but not significant effect on Audit Quality; (2) Auditor Competency has a positive and significant effect on Audit Quality; (3) Time Budget Pressure has a positive and significant effect on Audit Quality..